The Generics (UK) Case : a competition law analysis of patent settlement agreements in the pharmaceutical sector - Hashani, Vehap (2022)
The pharmaceutical industry is responsible for the development, production, and marketing of medications. Up to this date, this industry continues to develop and manufacture drugs to control and eliminate diseases. The market is filled with pharmaceutical products from companies worldwide, which have lost their patent protection or are ready to lose it. Whenever this might happen, generic manufacturers are expected to produce the same but cheaper versions of the prepatented drugs. Therefore, this situation that is beneficial for the consumer may pose tremendous competitive pressure to the originators who want to keep their blockbuster medicine's prolific dividends, hindering the competition by limiting the independent entry of the generics. The generics usually start their preparations years before the originator's patent expiry date and try to enter the market the moment it expires. During this period, patent disputes arise, which are time-consuming, costly, and complex and bring along uncertainties for both parties. Therefore, parties are incentivised to settle their disputes with an agreement that would benefit them simultaneously. These settlement agreements are typical for the pharmaceutical world since these settlements involve a payment from the originator to the alleged infringer, the generic, who in return delays its plans to enter the market the moment the patent expires. These arrangements are known as either reverse-payment or pay-for-delay settlements. The Commission only after 2009 has concluded that these settlements may restrict competition according to Article 101. After the inquiry, the Commission set out the three-step criteria, according to which the collusive settlements were considered restrictive by object within the meaning of Art. 101. According to the EU competition law, an agreement under restriction by object automatically is presumptively illegal, and as such, its background, motives, and effects are excluded from any further scrutiny. Therefore the purpose of this thesis is to critically analyse the approach taken by the Commission and national authorities, by studying the Generics (UK) ECJ’s judgment, in order to clarify whether other realistic factors that may induce parties to conclude a presumptively illegal settlement should be taken into consideration under EU Competition Law.